Molecular structure retrieval directly from laboratory-frame photoelectron spectra in laser-induced electron diffraction - Sanchez, A.; Amini, K.; Wang, S.-J.; Steinle, T.; Belsa, B.; Danek, J.; Le, A. T.; Liu, X.; Moshammer, R.; Pfeifer, T.; Richter, M.; Ullrich, J.; et al. (My University, 2021)
Ubiquitous to most molecular scattering methods is the challenge to retrieve bond distance and angle from the scattering signals since this requires convergence of pattern matching algorithms or fitting methods. This problem is typically exacerbated when imaging larger molecules or for dynamic systems with little a priori knowledge. Here, we employ laser-induced electron diffraction (LIED) which is a powerful means to determine the precise atomic configuration of an isolated gas-phase molecule with picometre spatial and attosecond temporal precision. We introduce a simple molecular retrieval method, which is based only on the identification of critical points in the oscillating molecular interference scattering signal that is extracted directly from the laboratory-frame photoelectron spectrum. The method is compared with a Fourier-based retrieval method, and we show that both methods correctly retrieve the asymmetrically stretched and bent field-dressed configuration of the asymmetric top molecule carbonyl sulfide (OCS), which is confirmed by our quantum-classical calculations.